INVENTARISASI JENIS-JENIS MAKROALGA DI PANTAI LHOK BUBON KECAMATAN SAMATIGA KABUPATEN ACEH BARAT - Sufal Diansyah; Ika Kusumawati; Fandi Hardinata (JURNAL PERIKANAN TROPIS, 2018)
Indonesia has tropical marine waters rich in biodiversity. One of the organisms living in Indonesian coastal waters is macroalgae. Algae is one of the marine natural resources of economic value and has an ecological role as a high producer in the food chain and spawning place of marine biota. types of macroalgae have many benefits, ecologically and economically for the community. The ecological benefits of macroalgae are to provide habitat for several types of marine life such as species of crustaceans, mollusca, echinoderms, fish or other small algae. The economic value of macroalgae can be used as food, industrial raw materials, and materials for laboratories such as wet preserved materials, media materials for bacterial and fungal breeding to produce antibiotics, and there are also macroalgal types used as medicines. This study aims to identify and inventory the types of macroalgae in Lhok Bubon waters. The research method used is survey method, by identifying macroalga and inventory of macroalga contained in research location. The results of identification of macroalgae in Lhok Bubon waters are Caulerpa racemosa, Chaetomorpha anteninna, Halimeda micronesica, Boegesenia forbesi, Cladhopora hespetica,  Halimeda discoidea, Chaetomorpha sp, Sargasum sp., Sargasum natans, Padina australis, Turbinaria ornata,  Canistrocaptus crispatus, Asparagopsis taxiformis, Galaxaura filamentosa,  dan Halymenia durvillei.